A past–present–future lens of environmental change: blending applied paleoecology and participatory system dynamics modeling at a conservation site in the Cape Floristic Region, South Africa - Forbes, Cherié Janine; Clifford-Holmes, Jai; Gillson, Lindsey (Frontiers in Conservation Science, 2024)
Landscapes are social-ecological systems (SESs) that produce ecosystem services, which change over time in response to environmental, biotic and social drivers. Failure to consider this variability, and the feedbacks that can stabilize or de-stabilize systems, can have consequences for sustainable ecosystem services provision. This study applies a conceptual meta-framework, past-present-future lens, to interpret changes in land cover and ecosystem services within the Cape Floristic Region (CFR) of South Africa. Palaeoecology (fossil pollen, spores and charcoal) and participatory system dynamics modelling were used to explore long-term variability in provisioning ecosystem services (plant biodiversity), and the drivers of this variability (fire and herbivory) at Elandsberg Private Nature Reserve (Elandsberg PNR). The palaeoecological record suggests that from ca. 1800s environmental changes, particularly a transition to unpalatable Elytropappus-dominated vegetation, were driven by grazing and that an ecological threshold was crossed in ca. 1950s due to agricultural intensification. Participatory system dynamics was used to identify feedbacks in the dynamic SES structure. The Ecological Model replicates these results and furthermore suggests that returning the system to within historical ranges variability may be difficult if this is what reserve managers desirerequire sustained reductions in both grazing and fire over decades. This innovative approach blends palaeoecology and participatory system dynamics to provide evidence-based understanding of temporal variability and feedbacks for policymakers and land-use managers to inform sustainable land management.